Hypoxaemia in acute respiratory and non-respiratory illnesses in neonates and children in a developing country. Issue 2 (1st February 2002) - Duke, T; Blaschke, A J; Sialis, S; Bonkowsky, J L
Abstract : Aims: To determine, in sick neonates and children requiring admission to a hospital in the highlands of Papua New Guinea: (1) the incidence and severity of hypoxaemia; (2) the proportion with hypoxaemia who do not fulfil criteria for acute lower respiratory infection (ALRI); and (3) the power of clinical signs to predict hypoxaemia, according to age and disease category. Methods: Age dependent normal values for transcutaneous oxygen saturation (Spo 2 ) were established in 218 well neonates and children in Goroka. A total of 491 sick neonates and children were then studied on presentation to the paediatric department at Goroka Hospital. Results: A total of 257 sick neonates and children (52%) were hypoxaemic. Hypoxaemia was present in 179/245 (73%) with clinical criteria for ALRI; 79/246 (32%) with non-ALRI illnesses (including meningitis, septicaemia, severe malnutrition, low birth weight, birth asphyxia, and congenital syphilis) were also hypoxaemic. For children aged 1 month to 5 years with ALRI, the clinical signs best predicting hypoxaemia were cyanosis, respiratory rate >60, poor feeding, or reduced spontaneous activity; in those without ALRI the best predictors were cyanosis, respiratory rate >60 per minute, and inability to feed, but the positive predictive value was much lower than for children with ALRI. For neonates cyanosis was predictive of hypoxaemia, but tachypnoea or inability to feed were not. Conclusions: Hypoxaemia is an under recognised complication of non-ALRI illnesses in children and in sick neonates in developing countries. Use of algorithms with high sensitivity for the recognition of hypoxaemia, and protocols for administration of oxygen to neonates, and to children with non-ALRI illnesses, might substantially reduce case fatality.